NMU DNA methylation in blood is associated with metabolic and inflammatory indices: results from the Moli-sani study - Annalisa Marotta; Fabrizia Noro; Roberta Parisi; Alessandro Gialluisi; Alfonsina Tirozzi; Amalia De Curtis; Simona Costanzo; Augusto Di Castelnuovo; Chiara Cerletti; Maria Benedetta Donati; Giovanni de Gaetano; Licia Iacoviello; et al. (Epigenetics, 2021)
Neuromedin U (NMU) is a neuropeptide involved in gut-brain axis, energy balance and immune response. We aimed at analysing the association between NMU epigenetic variability and metabolic indices and the potential mediating role of low-grade inflammation in a general population of Italian adults. NMU Blood DNA methylation levels at two CpG islands (NMU76 and NMU32) were analysed using pyrosequencing in a randomly selected sub-cohort of 1,160 subjects from the Moli-sani study (≥35years; 49.20% men). Multivariable regressions adjusted for age, sex, smoking, alcohol and vegetable consumption were performed to estimate the associations between methylation and metabolic phenotypes (BMI, waist-to-hip ratio, blood pressure, glucose, HOMA-IR, lipids, lipoprotein(a) and apolipoproteins). Mediation analysis was performed to identify the influence of low-grade inflammation in the association using a composite index based on C reactive protein, granulocyte-to-lymphocyte ratio (GLR), platelet and white blood cell counts (INFLA-score). Using principal component analysis four methylation factors were identified: NMU76-F1, NMU76-F2, NMU32-F1 and NMU32-F2. NMU76-F1 was FDR significantly associated with total cholesterol (for 1 SD increase: β = 4.5 ± 1.4 mg/dL of, R2 = 10.8%, p = 0.001), ApoB (0.03 ± 0.01 g/L, 12.2%, p = 0.0004), with INFLA-score (1.05 ± 0.22, p = 2.7E-6) and GLR (-0.27 ± 0.03, 30.4%, p = 1.3E-20). GLR and lymphocyte numbers mediate the association of NMU76-F1 with cholesterol (24.0% of total effect, Sobel p = 0.013) and ApoB (42.6%, p = 9E-7), respectively. These findings suggest that NMU promoter methylation patterns could mark a pathway linking lipids with haematopoiesis and systemic inflammation.